Prototype of Sinkhole Detection Model with Sensor Alarm - Norikman Norhadi; Haminozain, Nazri; Maisarah Husna; Muhammad Azim Mohammad Azmi (Multidisciplinary Applied Research and Innovation, 2026)
Sinkholes are a serious geological hazard that can disrupt public services, damage infrastructure, and even lead to fatalities. These events can occur suddenly and without visible warning, making early detection critical for risk mitigation and public safety. This study introduces a prototype sinkhole detection model designed to address this need through the integration of sensor technology and a real-time warning system. This model uses sensors to continuously monitor key geotechnical parameters such as soil moisture, ground vibration, and pressure changes. These parameters are known indicators of ground instability that could signal potential sinkhole formation. Sensor data are processed in real time using advanced analytical methods to detect significant changes in soil conditions. To evaluate the effectiveness of the prototype, the model is rigorously tested under controlled conditions. Simulated sinkhole scenarios are created to mimic real-world situations, allowing researchers to assess the system’s responsiveness and accuracy. The results of these tests indicate that the model can reliably identify early signs of sinkhole development and trigger timely alerts. By demonstrating strong performance during testing, this prototype shows promise as a practical, scalable, and cost-effective solution for sinkhole detection. This research contributes to improving geotechnical safety by enabling proactive measures and reducing the potential impact of sinkholes